Viability of UAV thermal imaging for geothermal power plant surveying - Eli Alexander Knox 1995- (2024)
This study examines the viability of using a consumer level drone based thermal imaging for geothermal power plant surveying. The equipment for this study was intentionally kept at low cost to examine the extent of features possible with minimal initial investment. A consumer level drone has also been selected due to ease of use, packaging of the drone and thermal imaging as one unit and availability of processing software. Using the thermal imaging camera of the UAV, the components of three geothermal power plants were examined. The mapping targeted primarily external features of power plants, such as distribution pipelines, re-injection pipelines, well heads, mixers, and condensers. In preparation for and throughout the thermal mapping process, challenges, and limitations due to weather conditions, geographical location and material types were examined. Adequate preparation is key in successful thermal mapping. The challenges are weighted against the benefits to evaluate the viability of thermal mapping for geothermal power plant located in Iceland. Tips are provided on additional considerations for drone based thermal mapping in other regions. Results from thermal mapping were examined for anomalies that are visible in the thermal (infrared) spectrum of light, but not evident to the naked eye. Thermal imaging has identified definitive locations of thermal leakage, this was further confirmed and identified as fluid leaks within the distribution pipeline envelope.